Selected aspects of a university’s sustainable development strategy - Napiecek, Remigiusz (Wybrane aspekty strategii zrównoważonego rozwoju uczelni wyższej, 2019)
The introduction of the Constitution for Science has initiated a series of changes in universities in Poland. Particularly important are changes which will conform to the universities’ structure to the new evaluation criteria, and consequently will affect their financial conditions. The concerns presented in the article refer to the sustainable development strategy of a university. This strategy should enable universities not to assess all of their research and educational employees according to the same criteria or according to the same threshold values. All academic teachers work for the success of the university, however, each of them to a different degree. This differentiation may result not only from the individual predispositions of employees but also from the adopted strategic assumptions. The article aims to present some aspects of the implementation of a university’s strategy with regard to subsidies granted under the Law on Higher Education and Science in Poland
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2019; vol. 63, nr 5, s. 163-172
Keywords: university; strategy; research activity; sustainable development; uczelnia wyższa; ustawa 2.0; strategia zrównoważonego rozwoju; subwencja